Rule of Love and Rule of Faith in Augustine’s Hermeneutics: A Complex Dialectic of the Twofold Rules - Yong, Steven (Sekolah Tinggi Teologi SAAT, 2021)
Since the sixteenth-century Reformation, literal interpretation of the Bible has been deemed the best hermeneutical method to unearth the biblical writers’ original meaning. For the Reformers, allegorical interpretation was denigrated for reading an extraneous, or spiritual, meaning into any text. Although Augustine was among the first who champions a literal interpretation of the Scripture—as he outlined in his De doctrina christiana—until recent decades, Augustine is still being perceived as inconsistent in following his hermeneutical method as it is attested in his interpretation of the Good Samaritan. In his interpretation, Augustine seems to have allegorized the parable, thus his method was accused of being inconsistent. Is it really the case? This article attempts to contest such an accusation by showing that Augustine’s method of interpretation cannot simply be categorized as either entirely literal or allegorical. Augustine never professes as a literalist, an exegete who only applies what is now known as a historical-critical method. On the other hand, he did not recklessly legitimate the application of allegorical reading to any text. Taken as a whole, Augustine’s hermeneutics revolves around a complex dialectic of regula dilectionis (the rule of love) and regula fidei (the rule of faith) that allows both interpretations to be considered to be true.